A systematic review of outcomes after revision amputation for treatment of traumatic finger amputation - Yuan, Frank (Plast Reconstr Surg, 2015)
BACKGROUND: Revision amputations are often the treatment for traumatic finger amputation injuries. However, patient outcomes are inadequately reported, and their impact poorly understood. We performed a systematic review to evaluate outcomes of revision amputations and amputation wound coverage techniques. METHODS: We searched all available English literature in PubMed and EMBASE for articles reporting outcomes of non-replantation treatments for traumatic finger amputation injuries, including revision amputation, local digital flaps, skin grafting, and conservative treatment. Data extracted were study characteristics, patient demographic data, sensory and functional outcomes, patient-reported outcomes (PROs), and complications. RESULTS: 1659 articles were screened, yielding 43 studies for review. Mean static 2-point discrimination (2-PD) was 5.0 ± 1.5 mm (n=23 studies) overall. Mean static 2-PD was 6.1 ± 2.4 mm after local flap procedures and 3.8 ± 0.4 mm after revision amputation. Mean total active motion (TAM) was 93 ± 8% of normal (n=6 studies) overall. Mean TAM was 90 ± 9% of normal after local flap procedures and 95% of normal after revision amputation. 77% of patients report cold intolerance after revision amputation. 91% of patients (217/238) report “satisfactory” or “good/excellent” ratings regardless of treatment. CONCLUSION: Revision amputation and conservative treatments result in better static 2-PD outcomes compared to local flaps. All techniques preserve TAM, although arc of motion is slightly better with revision amputation. Revision amputation procedures are frequently associated with cold intolerance. Patients report “satisfactory,” “good,” or “excellent” ratings in appearance and quality of life with all non-replantation techniques. LEVEL OF EVIDENCE: III